DAYA SAING LADA HITAM DI KECAMATAN ABUNG TINGGI KABUPATEN LAMPUNG UTARA - Meliyana, Rossika; Zakaria, Wan Abbas; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The research goals were to discover: the competitiveness of black pepper and the effects of black pepper declines, rising input prices, exchange rate appreciation, and the intensification of commodity on competitiveness of black pepper in Abung Tinggi Subdistrict, of North Lampung Regency. This research was conducted in Ulak Rengas Village, Abung Tinggi Subdistirct of North Lampung Regency using survey method in August 2012 – April 2013. The respondents of this research were 26 farmers of 286 black pepper farmers. The respondents were chosen using classified random sampling according to the age of their black pepper plants. The data were analyzed using Policy Analysis Matrix (PAM) to find out the competitiveness, and using sensitivity analysis to find out the level of sensitivity of competitiveness. The results showed that black pepper in Abung Tinggi Subdistrict of North Lampung Regency was competitive (PCR = 0.76, and DRCR = 0.65), the competitiveness of black pepper was sensitive to 50% decline in black pepper price and the intensification of black pepper, but the competitiveness was not sensitive to the increase in input prices (urea: 33%, TSP: 29%, KCl : 25%) and to 5.60% exchange rate appreciation. Key words: competitiveness, black pepper, PAM